Implementación del manual de uso y reúso de dispositivos odontológicos en el área de endodoncia, en las clínicas de la universidad Antonio Nariño sede Cúcuta (2022)
The use and reuse of instruments in the endodontic area allows verifying that the instrument has been disinfected and sterilized, in addition to verifying that its active part is still usable for the correct execution of treatments, with the aim of avoiding possible cross contamination. , in addition to guaranteeing the success of the procedures.